Municipios y gestion forestal en el tropico Boliviano - Balanza, P.P.; Kaimowitz, D. (CIFOR, Centro de Estudios para el Desarrollo Laboral y Agrario, Teller de Iniciativas en Estudios Rurales y Reforma Agraria, Bolivia Sustainable Forest Management Project, 1998)
This book looks at the role of municipal governments in lowland Bolivia in forest management since passage of a popular participation law in 1994 and a new forestry law in 1996. It covers issues related to logging, protected area management, land use planning, indigenous territories, and non-timber forest products. Most of the book consists of nine case studies of specific municipalities or groups of municipalities. The book concludes that decentralisation has opened new opportunities for more equitable access to forest resources and their benefits, but that local people’s capacity to take advantage of these opportunities varies. Initial indications point to both positive and negative effects on natural resource management, but it remains too early to determine whether the net impact of decentralisation on forests will be positive or negative. (DK)